Implementasi SEMA Nomor 1 Tahun 2022 Tentang Dikabulkannya Gugatan Perceraian Perspektif Sadd al-Żarī’ah: Implementation of SEMA Number 1 Year 2022 on the Granting of Divorce Suits from the Perspective of Sadd al-Żarī’ah - Wildan Zulfikar Rasyid (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
In a matrial relationship, sometimes promblems arise that result in divorce. If there is a dispute that cannot be resolved, Law Number 1 Year 1974 gives the right to file a divorce lawsuit. The Supreme Court issued Circular Letter (SEMA) Number 1 of 2022 which regulates the requirements for divorce, but is not legally binding. The purpose of this study is to analyze how the impact of the enactment of SEMA Number 1 of 2022 on wises who file for divorce in the perspective of sadd al-żarī’ah. This research uses a normative juridical method with an Islamic legal approach, namely ta’lilī. Based on the results of the research, the enforcement of SEMA Number 1 of 2022 can cause mafsadat. The enforcement of SEMA allows husband to commit domestic violence (KDRT) which threatens the safety of the wife. This contrary to the maqāṣid al-syarī’ah, namely hifẓ al-nafs (self-preservation). The basic consideration of sadd al-żarī’ah is to look at the results and consequences of an action. Thus, in accordance with the concept of sadd al-żarī’ah, the enactment of SEMA Number 1 of 2022 can change its law to be prohibited, because it has a mafsadat impact on the wife.